If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(130 + -1x) = 4125 (130 * x + -1x * x) = 4125 (130x + -1x2) = 4125 Solving 130x + -1x2 = 4125 Solving for variable 'x'. Reorder the terms: -4125 + 130x + -1x2 = 4125 + -4125 Combine like terms: 4125 + -4125 = 0 -4125 + 130x + -1x2 = 0 Factor a trinomial. (-75 + x)(55 + -1x) = 0Subproblem 1
Set the factor '(-75 + x)' equal to zero and attempt to solve: Simplifying -75 + x = 0 Solving -75 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '75' to each side of the equation. -75 + 75 + x = 0 + 75 Combine like terms: -75 + 75 = 0 0 + x = 0 + 75 x = 0 + 75 Combine like terms: 0 + 75 = 75 x = 75 Simplifying x = 75Subproblem 2
Set the factor '(55 + -1x)' equal to zero and attempt to solve: Simplifying 55 + -1x = 0 Solving 55 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-55' to each side of the equation. 55 + -55 + -1x = 0 + -55 Combine like terms: 55 + -55 = 0 0 + -1x = 0 + -55 -1x = 0 + -55 Combine like terms: 0 + -55 = -55 -1x = -55 Divide each side by '-1'. x = 55 Simplifying x = 55Solution
x = {75, 55}
| 3x+5=28-2x | | x-x^2=130 | | 9x+11=4x+1 | | -5(n-5)+7(n+1)= | | 4(x-3)+2(x-1)= | | -10(a+3)+6a= | | 7c-15-5c+42= | | 12-2c=2whatisc | | 6(n+3)+2n= | | -7(y-11)= | | -5+6c-5c= | | 5(1+3x)=125 | | -3n+8+8n= | | 40h+25k+35= | | -8c+c= | | -3a+11a= | | 305=0.15x+16y | | 9=2y-(2y-9) | | 2(x+15)=16 | | 305=0.15y+16x | | (7x+3y)-(2x-3y)= | | 10m-8m= | | -12-15x=3 | | 6(6+3x)=54 | | 24x+24y= | | -4(r-4s-9t)= | | 19.6t^2-14t+8=0 | | 45(-11-32)=c | | x-5=2(23.5)+12 | | -8(2t+6)=-112 | | 16=y+2 | | 2(4x-2)=7x |